COMMUNITY PARTICIPATION IN THE PLANNING AND IMPLEMENTATION OF CSR PROGRAMS: A CASE STUDY OF PT PELABUHAN INDONESIA IV MAKASSAR - Wardah, Siti Syarifah Wafiqah; Syarifuddin, Syarifuddin; Anwar, Muh Chaerul (Social Landscape Journal, 2025)
This study aims to analyze community participation in the planning and implementation of Corporate Social Responsibility (CSR) programs of PT Pelabuhan Indonesia IV (Pelindo IV) Makassar. The research is grounded in Indonesia’s mandatory CSR regulatory framework as stipulated in Law No. 40 of 2007, Government Regulation No. 47 of 2012, and the latest SOE regulations emphasizing sustainability and community empowerment. Although these regulations are legally binding, various studies highlight that the success of CSR implementation largely depends on community involvement from the planning to the implementation stages. This research employs a qualitative approach with a case study method, conducted in the area surrounding Makassar Port, particularly Kaluku Boddoa Subdistrict. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using the Miles and Huberman model combined with Arnstein’s Ladder of Participation and Pretty’s Typology of Participation. The findings reveal that community participation in planning remains at the tokenism level, limited to surveys and socialization, while in implementation it has developed towards functional and even interactive participation through MSME empowerment and social assistance programs. The main barriers include top-down communication and limited time availability, while the driving factors are program relevance to local needs and intensive mentoring. These findings underscore the need to shift from symbolic to substantive participation, so that CSR is not merely a legal obligation but also a sustainable instrument of community empowerment.